The new proxemics: COVID-19, social distancing, and sociable space - Mehta, Vikas (Journal of urban design, 2020)
Social distancing measures during COVID-19 have altered the use of space. With the closure of places of work, learning, leisure, consumption, and more, the pandemic has limited our territories and public life. Yet, residents living in mid- to low-density places are experiencing their neighbourhoods differently. They are repurposing residential streets, sidewalks, parking lots, and other spaces and transforming neighbourhood space for active living, play, and sociability. In many neighbourhoods, social distancing is generating a new sociable space. Can we build on our ingenuity to reclaim neighbourhood spaces for public life, and the physical and psychological health of our communities?